Willingness to Fund Public Education in a Rural, Retirement Destination County - Christopher D. Clark; Dayton M. Lambert; William M. Park; Michael D. Wilcox (Journal of Research in Rural Education, 2009)
Retiree recruitment is a burgeoning economic development strategy among rural communities despite uncertainty over whether later-life migrants will bring with them "Gray Gold" in the form of economic development or "Gray Peril" in the form of a reduced willingness to support the provision of local public services such as education. The results of a survey regarding support for a hypothetical increase in education funding in a rural, retirement destination county in Tennessee indicates that residents who migrated to the county at or after retirement were not less, but more, supportive of local education funding than other residents. The results also suggest that this support was motivated by both altruism and selfinterest. Previous experience in higher-funding jurisdictions was also a key factor in explaining migrant willingness to support increased expenditures. Finally, as a check on the validity of the survey instrument, a comparison is made between the aggregate survey results and the results of three county-wide referenda on school funding.